PERBANDINGAN AIR KELAPA DAN JUS SEMANGKA TERHADAP TINGKAT KEBUGARAN ATLET BASKET REMAJA SMA NEGERI 3 SAMARINDA - Wijdaniah, Anis; Utami, Riana Pangestu; Mulyani, Rieska Indah (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
The purpose of this study was to evaluated the impact of giving coconut water and watermelon juice on fitness level athletes fitness. This research used a Quasi Experimental Design with a pre- and post-test design with 22 teenage basketball athletes from SMA Negeri 3 Samarinda as subjects. The treatment is given to provide 200 ml of coconut water every 15-20 minutes during a moderate intensity training session for 3 consecutive days. Measurement of fitness levels was carried out by measuring the athlete's VO2max. VO2max was measured using the Bleep Test method at the beginning and the end of treatment. The results of the bivariate analysis using the Wilcoxon statistical test showed that giving coconut water to the fitness level of teenage basketball athletes from SMA Negeri 3 Samarinda had a significant effect with a p-value of 0.011 (p <0.05). and giving watermelon juice had a significant effect on the fitness level of teenage basketball athletes from SMA Negeri 3 Samarinda with a p-value of 0.024 (p <0.05). The results of the bivariate analysis using the Mann Whitney statistical test showed that there was no difference in the fitness level of teenage basketball athletes from SMA Negeri 3 Samarinda in the coconut water treatment group and the watermelon juice treatment group with a p-value 0.607 (p>0.05).